2023
DOI: 10.2147/jir.s401451
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nomogram Models Based on Peripheral Blood Score and Clinicopathological Parameters to Predict Preoperative Advanced Stage and Prognosis for Epithelial Ovarian Cancer Patients

Abstract: Nutritional and inflammatory states are crucial in cancer development. The purpose of this study is to construct a scoring system grounded on peripheral blood parameters associated with nutrition and inflammation and explore its value in stage, overall survival (OS), and progression-free survival (PFS) prediction for epithelial ovarian cancer (EOC) patients. Patients and Methods: Four hundred and fifty-three EOC patients were retrospectively identified and their clinical data and relevant peripheral blood para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The nomogram was further modified to increase the clinical utility of BRS. It showed higher AUC values compared to BRS alone, and exceeding the predictive power of a nomogram also based on peripheral blood features constructed by Bai et al [ 48 ], implying a higher predictive value for prognostic prediction in OC patients, which suggested that it may be a promising alternative metric for assessing prognostic risk in clinical OC.…”
Section: Discussionmentioning
confidence: 77%
“…The nomogram was further modified to increase the clinical utility of BRS. It showed higher AUC values compared to BRS alone, and exceeding the predictive power of a nomogram also based on peripheral blood features constructed by Bai et al [ 48 ], implying a higher predictive value for prognostic prediction in OC patients, which suggested that it may be a promising alternative metric for assessing prognostic risk in clinical OC.…”
Section: Discussionmentioning
confidence: 77%
“…Notably, our nomogram area under the curve (AUC) (0.803, 95% CI, 0.673–0.932; 0.869, 95% CI, 0.757–0.981) (Fig. 4 C) used to predict 1- and 3-year PFS for EOC patients was significantly higher than the AUC of other nomograms [ 46 , 47 ]. On the basis of the existing necessary detection items of EOC, incorporating easy-to-detect CD47 IHC score makes our model low-cost and convenient application.…”
Section: Discussionmentioning
confidence: 81%
“…For example, FIGO III-IV was identified as one independent prognostic factor for OS and PFS in OC patients in research by Bai et al. ( 27 ). In addition, a SEER database –based study proposed FIGO staging as an independent prognostic factor for malignant germ cell tumours of the ovary ( 28 ).…”
Section: Discussionmentioning
confidence: 99%